CULTURAL DIMENSIONS OF ENVIRONMENTAL PROBLEMS: A CRITICAL OVERVIEW OF SOLID WASTE GENERATION AND MANAGEMENT IN NIGERIA - Albert, Ajani Oludele; Olutayo, Fakunle Sunday (American International Journal of Multidisciplinary Scientific Research, 2021)
Several studies have presented solid waste generation and management in urban centres as an engineering and technological concern. These studies neglected culture as the basic determinants of all happenings in human society; hence, the cultural facets of solid waste generation and management were rendered insignificant. As culture provides the context within which all human activities take place, culture was envisaged in this paper as a driving force for public perception, decision making and participation in solid waste generation and management in urban centres. Therefore, this study adopted both meta-analysis and meta-synthesis to pinpoint and discuss some theoretical key cultural factors and social practices influencing municipal solid waste generation and management. It identified trends and relationship between findings from the available empirical and theoretical studies. This paper discovered in the available relevant literature that cultural factors such as customs, belief and attitude of the urbanites that promoted their preference for food packaged with non-biodegradable material and the ways they conducted social practices resulted in solid waste generation. Lastly, methods and the cost of solid waste disposal, individualism and nonchalant attitude of people were found as the factors militating against proper management of solid wastes.